Mechanical thrombectomy for emergent large vessel occlusion: a critical appraisal of recent randomized controlled clinical trials - Tsivgoulis, Georgios; Safouris, Apostolos; Katsanos, Aristeidis H; Arthur, Adam S; Alexandrov, Andrei V (Brain and behavior, 2016)
BACKGROUND AND PURPOSE: After numerous attempts to prove efficacy for endovascular treatment of ischemic stroke, a series of recent randomized controlled clinical trials (RCTs) established fast mechanical thrombectomy (MT) as a safe and effective novel treatment for emergent large vessel occlusion (ELVO) in the anterior cerebral circulation. METHODS: We reviewed five recent RCTs that evaluated the safety and efficacy of MT in ELVO patients and captured available information on recanalization/reperfusion, symptomatic intracranial hemorrhage (sICH), clinical outcome, and mortality. MT was performed with stent retrievers, aspiration techniques, or a combination of these endovascular approaches. We applied meta-analytical methodology to evaluate the pooled effect of MT on recanalization/reperfusion, sICH, functional independence (modified Rankin scale score of 0-2) and 3-month mortality rates in comparison to best medical therapy (BMT). RESULTS: MT was associated with increased likelihood of complete recanalization/reperfusion (RR: 2.22; 95%CI: 1.89-2.62; P < 0.00001) and 3-month functional independence (RR: 1.72; 95%CI: 1.48-1.99; P < 0.00001) without any heterogeneity across trials (I (2) = 0%). The absolute benefit increase in MT for complete recanalization/reperfusion and functional independence was 44 (NNT = 2) and 16 (NNT = 6), respectively. MT was not associated with increased risk of 3-month mortality (15% with MT vs. 19% with BMT) and sICH (4.6% with MT vs. 4.3% with BMT), while small heterogeneity was detected across the included trials (I (2) < 25%). CONCLUSIONS: MT is a safe and highly effective treatment for patients with ELVO in the anterior circulation. For every six ELVO patients treated with MT three more will achieve complete recanalization at 24 h following symptom onset and one more will be functionally independent at 3 months in comparison to BMT.
Keywords: Humans; Randomized Controlled Trials as Topic; mechanická trombolýza; Brain Ischemia; recanalization; thrombectomy; ischemic stroke; randomizované kontrolované studie jako téma; Stroke; cévní mozková příhoda; intravenous thrombolysis; ischemie mozku; Mechanical Thrombolysis; Endovascular treatment; lidé